Genetic analysis of resistance and virulence characteristics of clinical multidrug-resistant Proteus mirabilis isolates - Li, Ying; Yin, Ming; Fang, Chengju; Fu, Yu; Dai, Xiaoyi; Zeng, Wei; Zhang, Luhua (Frontiers in Cellular and Infection Microbiology, 2023)
Proteus mirabilis is the one of most important pathogens of catheter-associated urinary tract infections. The emergence of multidrug-resistant (MDR) P. mirabilis severely limits antibiotic treatments, which poses a public health risk. This study aims to investigate the resistance characteristics and virulence potential for a collection of P. mirabilis clinical isolates. Antibiotic susceptibility testing revealed fourteen MDR strains, which showed high resistance to most β-lactams and trimethoprim/sulfamethoxazole, and a lesser extent to quinolones. All the MDR strains were sensitive to carbapenems (except imipenem), ceftazidime, and amikacin, and most of them were also sensitive to aminoglycosides. The obtained MDR isolates were sequenced using an Illumina HiSeq. The core genome-based phylogenetic tree reveals the high genetic diversity of these MDR P. mirabilis isolates and highlights the possibility of clonal spread of them across China. Mobile genetic elements SXT/R391 ICEs were commonly (10/14) detected in these MDR P. mirabilis strains, whereas the presence of resistance island PmGRI1 and plasmid was sporadic. All ICEs except for ICEPmiChn31006 carried abundant antimicrobial resistance genes (ARGs) in the HS4 region, including the extended-spectrum β-lactamase (ESBL) gene blaCTX-M-65. ICEPmiChn31006 contained the sole ARG blaCMY-2 and was nearly identical to the global epidemic ICEPmiJpn1. The findings highlight the important roles of ICEs in mediating the spread of ARGs in P. mirabilis strains. Additionally, these MDR P. mirabilis strains have great virulence potential as they exhibited significant virulence-related phenotypes including strong crystalline biofilm, hemolysis, urease production, and robust swarming motility, and harbored abundant virulence genes. In conclusion, the prevalence of MDR P. mirabilis with high virulence potential poses an urgent threat to public health. Intensive monitoring is needed to reduce the incidence of infections by MDR P. mirabilis.